Festiwal muzyki ludowej w Gdyni. (Gdynia : [s.n.], 1949)
Afisz z programem festiwalu, który miał miejsce 8-26 maja 1949 r.
Keywords: Festiwale -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Życie artystyczne -- Polska -- Gdynia -- 1945-1970.; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła